The Use of Long Plate DHS for The Treatment of Subtrochanteric Fractures of Femur in Adults - KAZI M SAEED SAEED RAO, YAWAR ANIS (Journal of Fatima Jinnah Medical University, 2018)
Methods and Materials: A total of 120 subtrochanteric fractures of femur performed over a period of 7 years. Out of these 120 patients 100 were included in this study group and were followed up For at least two years. All were treated with long plate 135 degree DHS Results: All except 5 cases united within 6 months. There were three delayed unions .Two cases went into non union requiring subsequent re-operation. There were 2 implant failures. There were 3 infections which settled after implant removal. There were 3 malunions with shortening greater than 1.5 cm. All patients except 5 were fully weight bearing within 6 months. Discussion: All cases evetually united. There were only 3 malunions with shortening greater than 1.5 cm. There were three serious infections requiring removal of implants and they settled with implant removal. These results are comparable with any other treatment mode used for this fracture. Conclusion: All in all this is a cost effective and easy to perform treatment option for subtrochanteric fractures which provides satisfactory results.